Joint (participatory) Forest Management - Tewari, D. N. (Indian Forester, 1993)
Forestry is not simply a question of trees; it is above all a question of mankind. It is very difficult to impose forest conservation regulations on rural populations, when forest areas undergo pressures arising from the need to satisfy vital food, fodder, fibre and energy reqnirements. Meeting these basic needs is a priority. Foresters have to pay more attention to the expectations and needs of society and by involving the local population in managing the forest sustainably. A well-balanced physical, financial, human, natural, institutional and cultural commitment is the condition for joint forest management with durable success.